Prototype Design Analysis of Digital-Based Wind Tunnel Aerodynamic Testing Equipment - Bambang Setiawan; Rasma Rasma (Faculty of Engineering Universitas Muhammadiyah Jakarta, 2023)
The design of the prototype uses an electric motor / fan that can be adjusted to produce wind gusts in the wind tunnel. Measurement of dynamic pressure, static pressure and (for compressed flow only) temperature rise in the air stream. The direction of airflow around the model can be determined from the tufts of threads attached to the aerodynamic surface. An important Wind Tunnel design is the geometrical similarity of all dimensions of the object must be proportionally scaled, Mach number the ratio between the speed of air and the speed of sound must be identical for the scaled model and the actual object. the method used in the completion of the wind tunnel machine using the design concept of data collection techniques using solidwork. Making a wind tunnel model by determining the length of the test section of 0.50m, the length of the diffuser being 0.8m, the calculation of the contraction length of the contraction being 0.54m and the height of the contraction being 0.60m calculating the length The only gain is 0.096m Energy losses in the Wind tunnel of 0.02373, Energy Losses on the screen of 0.02373, Energy Losses in Contraction of 0.01728, Energy Losses in the test section of 0.05, Energy Losses on the diffuser of 0.04518 The result of the research that the wind using an anemometer is 2.9 m/s with a temperature of 32.4 °C. The style of getting the results of the airfoil test is that the first form has a drag force of 11.61 grams and a left force of 2.61 grams, while for the second form a drag force is obtained. of 11.50 grams and the left force of 2.50 grams. In this wind tunnel the maximum wind speed is 2.9 m/s, the average wind speed in Indonesia is 2.5 – 3 m/s. In the honeycomb, the wind is controlled so that the wind entering the tunnel becomes unidirectional or focused, and then enters the intake contraction, the wind is increased in pressure by reducing the size of the test section, the goal is to maximize the friction between the test object and the wind.